2016
DOI: 10.1371/journal.pcbi.1004749
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adherence and Retreatment in De Novo Emergence of MDR-TB

Abstract: Treatment failure after therapy of pulmonary tuberculosis (TB) infections is an important challenge, especially when it coincides with de novo emergence of multi-drug-resistant TB (MDR-TB). We seek to explore possible causes why MDR-TB has been found to occur much more often in patients with a history of previous treatment. We develop a mathematical model of the replication of Mycobacterium tuberculosis within a patient reflecting the compartments of macrophages, granulomas, and open cavities as well as parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 71 publications
(58 reference statements)
3
29
0
2
Order By: Relevance
“…In addition to providing in vivo evidence of the critical roles of multiple MHC-like-interacting iT cells in amphibian immunity, this study places X. laevis tadpoles as an attractive alternative animal model to explore the role of iT cells in establishment and persistence of Mtb, the causative agent of TB in humans. Despite years of research, Mtb remains a leading cause of infectious mortality worldwide and although TB is generally curable, current treatment strategies are complex and of long duration with the emergence of multidrug and extensive drug-resistant TB (35,36). Although it is well established that cellular immunity is critical in controlling mycobacterial growth, there are still major gaps in our understanding of how the early initiation and regulation of the immune response occurs (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing in vivo evidence of the critical roles of multiple MHC-like-interacting iT cells in amphibian immunity, this study places X. laevis tadpoles as an attractive alternative animal model to explore the role of iT cells in establishment and persistence of Mtb, the causative agent of TB in humans. Despite years of research, Mtb remains a leading cause of infectious mortality worldwide and although TB is generally curable, current treatment strategies are complex and of long duration with the emergence of multidrug and extensive drug-resistant TB (35,36). Although it is well established that cellular immunity is critical in controlling mycobacterial growth, there are still major gaps in our understanding of how the early initiation and regulation of the immune response occurs (37).…”
Section: Discussionmentioning
confidence: 99%
“…The short half‐life and sharp dose‐response curves for these drugs make the time spent in the selection window where resistant strains are favored small. Similar models have now been developed for many different infections, including HCV, HSV, TB, and others have applied similar models to HIV to examine effects such as archiving of transmitted resistant strains in the latent reservoir, tissue compartments with lower drug concentrations, details of intracellular pharmacokinetics of drugs, and host immunity.…”
Section: Modeling Antiretroviral Therapymentioning
confidence: 99%
“…Several studies such as a study done by Cadosch, et al have investigated the effects of adherence counselling and DOT on treatment outcomes. The results of that study showed that failure to adhere to anti-TB medication directly affects treatment outcomes [22]. Another study done in 2016 looked at the association between DOT and TB treatment outcomes and found that there was no statistical significance [17].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Moreover, the lack of adherence counselling as well as emotional and psychosocial support to TB patients and their families is linked to poor treatment outcomes including loss to follow-up and development of DR-TB [5] [18] [19]. The occurrence of adverse drug effects is more common among patients medication for DR-TB and DS-TB, which compromises adherence to medication [18] [20] [21] [22]. Thus, the World Health Organisation (WHO) identifies improved quality of adherence counselling as a key intervention under DOTS to improve medication adherence and TB treatment of outcomes [23] [24].…”
Section: Introductionmentioning
confidence: 99%